Distribution of Atmospheric Precipitation During the Year by Months and Seasons (Example of Bukhara Region) - Pirimova S.K. (Zien Journals, 2023)
This work is dedicated to the determination of changes in atmospheric precipitation by months and seasons during the year in the example of Bukhara region. In the implementation of the work, the information about the atmospheric precipitation observed at the meteorological observation points located in the studied area was used. As a result, it was determined that the rainfall in the region is unevenly distributed by months and seasons throughout the year.
Keywords: atmospheric precipitation; Bukhara region; meteorological station and posts; Jongeldi